Persepsi Keadilan Perpajakan dalam Pandangan Wajib Pajak - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to examine perceptions of tax fairness from the perspective of taxpayers based on a review of the literature. The research method used is descriptive qualitative with a literature study approach, with data sources in the form of textbooks, scientific journals, policy reports, and relevant tax regulations. The results of the study show that perceptions of tax fairness are an important factor that influences taxpayers' attitudes and behavior towards the tax system. Perceptions of fairness are not singular, but are shaped by several main dimensions, namely distributive justice, procedural justice, and interactional justice. Distributive justice relates to the distribution of the tax burden based on economic capacity, procedural justice relates to the transparency and consistency of tax regulations, while interactional justice relates to the quality of interaction between tax officials and taxpayers. In addition, transparency and the availability of tax information also play a role in strengthening perceptions of fairness. This study concludes that increasing tax compliance does not only depend on regulations and sanctions, but also on the government's efforts to build a fair, transparent, and service-oriented taxation system.